Mistake, fraud and duties to inform in European contract law - Sefton-Green, Ruth (Cambridge University Press, 2004)
Several chapters introduce the civil law tradition regarding mistake and misrepresentation, but the heart of the volume consists of 12 case studies illustrating the details and practicalities and allowing for comparison among countries. The cases involve such activities as the sale of a Monet painting by an unsuspecting old lady, the misrepresentation by an art gallery claiming "few restorations" on a statuette when in fact there were many, and a hastily signed contract by a consumer for a pan that would not work on her type of stove, among others. The editor offers a final chapter with comparative conclusions. This is the fifth volume in a series devoted to the case- description methodology undertaken by the Common Core of European Private Law project begun in 1993 at the U. of Trento.